ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KONSUMSI KOPI DI MALANG TAHUN 2022 (Studi Kasus: Jl. Ikan Tombro - Kota Malang) - Widya Chandra, Meina; Fadjar, Nurman Setiawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Indonesia as one of the countries passed by the equator and makes it a tropical country suitable for planting coffee beans. There is an increase in the level of coffee consumption both nationally and internationally. Coffee is currently a popular drink among the people, including the people in Malang, which are dominated by students (young age). Coffee shops are experiencing rapid growth in Malang, on Jl. Ikan Tombro forms a complex with a road that is approximately 300m long with 60 coffee shops along the way and forms a monopolistic market competition. This study aims to analyze the factors namely age (X1), income (X2), price (X3), coffee quality (4) and atmosphere (5) on the level of coffee consumption in Malang with a case study Jl. Ikan Tombro. The analytical method used in this study is multinomial logistic regression. The required number of respondents is 100 consumers from respondents with the criteria of having or are currently visiting a coffee shop on Jl. Ikan Tombro, Malang. The results of the research seen from the simultaneous test show that all variables have a positive significant effect on the level of coffee consumption.